A theoretical and experimental analysis of cold-formed steel shapes subjected to bending - Channel and simple lipped channel - Gonçalves, Roberto Martins; Malite, Maximiliano; Javaroni, Carlos Eduardo [UNESP] (My University, 2000)
Cold-formed steel shapes have been widely employed in steel construction, where they frequently offer a lower cost solution than do traditional laminated shapes. A classic application of cold-formed steel shapes is purlins in the roof panel of industrial buildings, connected to the roof panel by means of screws. The combined effect of these two elements has been the subject of investigations in some countries. Design criteria were included in the AISI Code in 1991 and 1996. This paper presents and discusses the results obtained from bending tests carried out on shapes commonly used in Brazil, i.e., the channel and the simple lipped channel, Tests were carried out on double shapes with 4.5 and 6.0 meter spans, which were subjected to concentrated loads and braced against each other on the supports and at intermediary points in three different load situations. The panel shape was also analyzed experimentally, simulating the action of wind by means of a vacuum box designed specifically for this purpose. The test results were then compared to those obtained through the theoretical analysis, enabling us to extract important information upon which to base proposed design criteria for the new Brazilian code.
Keywords: Cold-formed steel shapes; Lipped channels; Purlins; Wind suction; Buildings; Mathematical models; Roofs; Screws; Structural loads; Wind effects; Steel construction